Crossroads of the academy: advice from a sometimes mistaken, but victorious trajectory - Ivan Aprahamian (Brazilian Society of Geriatrics and Gerontology, 2023)
An academic trajectory is marked by victories and defeats, hits and misses. Each trajectory is personal and unique. It's common to find oneself at a crossroads, with no clear choice or segue to the next step. At such times, we rely on advice from mentors and peers. From this viewpoint, I discuss seven directives I believe to be important for everyone involved in academic life, especially those in biomedicine and young professors or researchers in geriatrics and gerontology: (1) be empathetic, (2) be available, (3) be studious, (4) be different, (5) be communicative, internationally, (6) always be a mentor and a mentee, and (7) be a leader (not a boss) as soon as possible. These directives have helped me over the past 20 years, and if someone had given them to me at the beginning of my career, I would have been much more successful and have enjoyed a much smoother, happier ride down this road, avoiding many wrong turns.